Application of Data Mining Method to Predict Soil Quality Based on Environmental Parameters - Marsya, Jiwa Malem (Cattleya Darmaya Fortuna, 2024)
Employee performance appraisal is an important aspect of human Soil quality is a critical factor in agriculture and environmental conservation, as it directly impacts agricultural productivity and ecosystem sustainability. Traditional methods of monitoring and evaluating soil quality based on environmental parameters, such as pH, moisture content, temperature, and humidity, can be time-consuming and costly. This research aims to explore the application of data mining techniques to predict soil quality using various environmental parameters. Data mining, particularly machine learning algorithms such as decision trees, support vector machines (SVM), and neural networks, allows for the extraction of hidden patterns and relationships in large datasets, providing an efficient approach for soil quality prediction. The study utilizes data from soil samples, including parameters like pH, moisture content, temperature, and other environmental variables, to develop predictive models. The effectiveness of different data mining techniques is evaluated based on their accuracy and efficiency in predicting soil quality. The results of this study are expected to contribute to the development of reliable and rapid tools for assessing soil quality, which could be applied in agricultural management, land conservation, and environmental monitoring.By leveraging data mining techniques, this research provides insights into the potential for improving soil management practices and supporting sustainable agriculture. The findings of this study may offer valuable recommendations for farmers, land managers, and environmentalists in making informed decisions for better land use and conservation strategies.